Willingness To Pay Petani Lada Di Provinsi Lampung - Nuni Anggraini; Dayang Berliana; Bambang Utoyo (Journal of Food System & Agribusiness, 2019)
Plantation commodities that play an important role in export and import activities were pepper. Based on Badan Pusat Statistik (2017), Indonesia the main supplier of black pepper to the United States market with a delivery rate of 20,423 metric tons (47%). Means that Indonesia's opportunities enormous in pepper trade and business. One of the obstacles encountered by pepper farmers difficulty in getting quality pepper seeds. The expensive price of pepper seeds was one of the factors in the difficulty of getting high-quality and high-quality plant material (Sutarman 2015). After selling the quality pepper seeds, an analysis of market response was needed, both in terms of market acceptance of these quality pepper seeds, as well as price responses from the pepper farmers themselves. This study aims to analyze the willingness of pepper farmers to pay for certified pepper seeds. This research was conducted in Way Kanan and North Lampung, which the centers of pepper production in Lampung. The number of respondents which was taken as a sample of 30 respondents. The used approached was a qualitative approach. Data collection techniques were direct observation (observation), in-depth interviews, questionnaires, and literature and documentation studies. The results showed that the value of the Willingness to Pay of consumer farmers was generally higher than the actual price, which was Rp 18,977.78. Keywords: pepper, seeds, VCM , Willingness to pay